CLIMATE HAZARDS AND LIVELIHOOD VULNERABILITY: AN EMPIRICAL ANALYSIS OF SOCIOECONOMIC RESILIENCE - PRIYANT BANERJEE; ARSHAD BHAT (Innovare Journal of Agricultural Sciences, 2025)
Climate change threatens vulnerable communities worldwide. With potential impacts reaching into livelihood systems that have sectors highly climate-sensitive – considering sectors like agriculture, fishing, and tourism – it is increasingly becoming recognized that climate hazards pose a potential threat to livelihoods in a significant way. This paper attempts to establish a statistical relationship between climate hazards – from flooding to droughts to cyclones – and vulnerability, focusing specifically on the socio-economic dimensions. Using regional and sectoral data from the Government and International Organizations, e.g., World Bank, UNDP, we construct an index of livelihood vulnerability, which incorporates some economic indicators such as income, employment, and access to social safety nets. Its patterns of resilience and susceptibility are outlined by statistical tools like regression analysis and factor analysis. While some sectors have become resilient because of governmental interventions and diversified income streams, there still exist other regions that remain vulnerable because of their poor adaptive capacity. Recommendations for policy with respect to improvements in resilience and reductions in vulnerability are offered, and based on the focus of this paper, it stresses the necessity of both integrated disaster management and socioeconomic planning.